The European Union and competitiveness - Eperjesi, Zoltán (Acta Agraria Debreceniensis, 2013)
I define first of all the competitiveness in my study „Analysing the competitiveness of the European Union”. After that I turn to the analysis of the competitiveness of the EU. The European competitiveness index and its concept were of great assistance during the analyses. The concept of the European competitiveness index has three main components: creative economy, economic performance, access to infrastructure. It is unambiguous that the European Union can only sustain and increase its position reached in the world economy, when its member states commit themselves for the completion of the knowledge based economic policy striving for competitiveness. The Europe 2020 strategy and the budget period 2007–2013 emphasize the outstanding role of competitiveness and urge to take the necessary measures.